The Involvement of the McsB Arginine Kinase in Clp-Dependent Degradation of the MgsR Regulator in Bacillus subtilis - Lilge, Lars; Reder, Alexander; Tippmann, Frank; Morgenroth, Friedrich; Grohmann, Janice; Becher, Dörte; Riedel, Katharina; Völker, Uwe; Hecker, Michael; Gerth, Ulf (Frontiers in Microbiology, 2020)
Regulated ATP-dependent proteolysis is a common feature of developmental processes and plays also a crucial role during environmental perturbations such as stress and starvation. The Bacillus subtilis MgsR regulator controls a subregulon within the stress- and stationary phase σB regulon. After ethanol exposition and a short time-window of activity, MgsR is ClpXP-dependently degraded with a half-life of approx. 6 min. Surprisingly, a protein interaction analysis with MgsR revealed an association with the McsB arginine kinase and an in vivo degradation assay confirmed a strong impact of McsB on MgsR degradation. In vitro phosphorylation experiments with arginine (R) by lysine (K) substitutions in McsB and its activator McsA unraveled all R residues, which are essentially needed for the arginine kinase reaction. Subsequently, site directed mutagenesis of the MgsR substrate was used to substitute all arginine residues with glutamate (R-E) to mimic arginine phosphorylation and to test their influence on MgsR degradation in vivo. It turned out, that especially the R33E and R94/95E residues (RRPI motif), the latter are adjacently located to the two redox-sensitive cysteines in a 3D model, have the potential to accelerate MgsR degradation. These results imply that selective arginine phosphorylation may have favorable effects for Clp dependent degradation of short-living regulatory proteins. We speculate that in addition to its kinase activity and adaptor function for the ClpC ATPase, McsB might also serve as a proteolytic adaptor for the ClpX ATPase in the degradation mechanism of MgsR.